Institutional Gridlock in Food Security Policy: A Neo-Institutionalist Analysis of Urban Food Governance in Indonesia - Dalimunthe, Ahmad Ridwan; Nurdin, Nurliah; Labolo, Muhadam; Simanjuntak, Tumpak Haposan (Dinasti Research, 2024)
This study examines the phenomenon of institutional gridlock in urban food security governance in Indonesia, focusing on the complexities of interactions among government institutions and their impact on policy effectiveness. Utilizing a neo-institutionalist approach, this research analyzes how institutional fragmentation, conflicts of interest, and the historical legacy of power centralization contribute to the formation of gridlock that hampers the effective implementation of food security policies in urban areas. Through comprehensive analysis of policy documents and academic literature, the study identifies patterns of institutional interaction, explores the manifestations and consequences of institutional gridlock, and evaluates the potential of institutional bricolage as a strategy to overcome existing structural barriers. The key findings indicate that institutional gridlock in this context results from the complex interaction between path dependency, institutional layering, and political fragmentation, which creates inertia against the necessary policy changes to address contemporary urban food security challenges. This study contributes to the development of a conceptual framework for understanding and addressing institutional gridlock in public policy governance in developing countries, particularly in the context of decentralization and rapid urbanization.